Host-parasite ecology, behavior and genetics: a review of the introduced fly parasite Philornis downsi and its Darwin's finch hosts. Issue 1 (December 2016) - Kleindorfer, Sonia; Dudaniec, Rachael
Abstract Understanding host-parasite interactions requires that the multi-faceted relationships among ecological, behavioral and molecular processes be characterized and integrated. The introduced parasitic fly of birds, Philornis downsi (Diptera: Muscidae), was accidentally introduced to the Galápagos Islands circa 1960s and the consequences of its introduction represent one of the most challenging conservation battles faced within host-parasite ecology today. Larvae of the fly were first discovered in nests of Darwin's finches (Passeriformes: Thraupidae) in 1997. The parasitic fly larvae are killing 55 % of Darwin's finch nestlings within nests by consuming the blood and tissue of developing birds, whereby the number of parasitic fly larvae in nests has increased by 46 % from 2000 to 2013. As nestlings increasingly die at an earlier age, which signifies earlier resource termination for the parasite, 17 % of fly larvae also die. Several local finch populations have become extinct but some host species have increased in abundance, and as a consequence, may be sustainingP. downsi populations along with other non-finch hosts. The high mortality in both Darwin's finches andP. downsi larvae creates opportunity and imperative to understand the coevolutionary dynamics of this newly evolving host-parasite system. This review examines the rapid changes in host and parasite ecology, behavior, and genetics sinceP. downsi larvae were first discovered in Darwin's finch nests. The aim of the review is to synthesize what is known about this lethal host-parasite system and to describe rapid changes in host and parasite biology that characterize the novel association. An over-arching goal is the implementation of conservation outcomes that are informed by evolutionary biological understanding of invasive species.